IMPLEMENTASI MATRIK EFE, MATRIK IFE, MATRIK SWOT DAN QSPM UNTUK MENENTUKAN ALTERNATIF STRATEGI GUNA MENINGKATKAN KEUNGGULAN KOMPETITIF BAGI USAHA PRODUKSI KELOMPOK BURUH PEMBATIK DI KESER NOTOG PATIKRAJA BANYUMAS - Sulasih, Sulasih (Politeknik Dharma Patria Kebumen, 2019)
The purpose of this research is to know the external and internal environmental factors by using the EFE and IFE matrix that lead to the competition changes and seek the alternative strategies by applying SWOT matrix as well as by specifying or selecting the most appropriate strategy through QSPM at Batik Labor Group Production on Keser Notog , Patikraja, Banyumas. This research implemented descriptive research based on the case study that applied qualitative and quantitative approach. The data collection related to the research was accomplished in several stages. It was started by interviews or Focus Group Discussion (FGD) by providing questionnaires to the concerned stakeholders. The data analysis was conducted through Internal Factor Evaluation (IFE) Matrix; External Factor Evaluation Matrix (EFE) Matrix; Strength, Weakness, Opportunity, Threat (SWOT); and Quantitative Strategic Planning Matrix (QSPM). The results of this study shows that the strategy on creating a unique styles and motifs of batik is the best alternative strategy to be implemented in Batik Labor Groups Production on Keser Notog, Patikraja, Banyumas, Central Java with the TAS value of 6.22 for QSPM matrix. This strategy is the most appropriate approach to be implemented to enhance the competitive advantage to face the various kinds of threats and weaknesses and to strengthen the competitiveness in business production of Batik in Keser Notog, Patikraja, Banyumas, Central Java.